2009
DOI: 10.1037/a0015435
|View full text |Cite
|
Sign up to set email alerts
|

Progress monitoring in oral reading fluency within the context of RTI.

Abstract: Selecting appropriate measures to make decisions about child response to intervention is a key concern. The most commonly used assessment tool in response to intervention (RTI) models is curriculum-based measurement (CBM). However, an issue related to the use of CBM is the identification of measures that are of similar difficulty. To the degree that variation in performance across measurement occasions can be attributed to anything other than student learning, errors in judgment about student RTI may be made. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 14 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…In this manner, an intervention requiring the fewest number of instructional minutes per unit of change is considered to be most efficient. The concept of efficiency also has been applied to academic assessment (Griffiths, VanDerHeyden, Skokut, & Lilles, 2009) and behavioral assessment (Volpe et al, 2009; Volpe & Gadow, in press), wherein the psychometric properties of more time-intensive assessment approaches have been compared to less time-intensive approaches. Here, if a less time-intensive method reaches the threshold for reliability or validity, it can be chosen over the more time-intensive method.…”
Section: Evaluating Rating Scales For Use In Problem-solving Modelsmentioning
confidence: 99%
“…In this manner, an intervention requiring the fewest number of instructional minutes per unit of change is considered to be most efficient. The concept of efficiency also has been applied to academic assessment (Griffiths, VanDerHeyden, Skokut, & Lilles, 2009) and behavioral assessment (Volpe et al, 2009; Volpe & Gadow, in press), wherein the psychometric properties of more time-intensive assessment approaches have been compared to less time-intensive approaches. Here, if a less time-intensive method reaches the threshold for reliability or validity, it can be chosen over the more time-intensive method.…”
Section: Evaluating Rating Scales For Use In Problem-solving Modelsmentioning
confidence: 99%
“…Reading referrals were clearly the most frequent type of referral reported by school psychologists. This finding is consistent with the large volumes of research in school psychology devoted to reading assessments and evidence‐based reading interventions (Baker, Gersten, & Grossen, 2002; Griffiths, Vanderheyden, Skokut, & Lilles, 2009; Shinn, 2008). Despite the heightened attention placed on both reading‐ and math‐based interventions in recent years, approximately 20% of the psychologists sampled in the current study indicated that professional development training in academic skills interventions was their top priority or most important area of need (see Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…One third of the sessions were audio recorded and checked for procedural integrity and interscorer agreement (Griffiths et al, 2009). The PI used an integrity checklist to determine whether all of the required procedures were followed.…”
Section: Methodsmentioning
confidence: 99%